2016
DOI: 10.1111/tesg.12186
|View full text |Cite
|
Sign up to set email alerts
|

Transport Supply and Demand Changes in Relation to Unemployment: Empirical Evidence from the Czech Republic in a Time of Crisis

Abstract: The continuing European recession underlines the urgency of the unemployment and labour force mobility issue. Therefore, the objective of this study is to scrutinise the relationship between changes in unemployment rate and transport indicators in the intercensal period 2001--2011. Both primary and secondary data are used in the analysis. Rate of car ownership and commuting data were taken from national censuses in 2001 and 2011 which surrounded the 2008 crisis. Primary data came from 1,023 interviews. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Three studies further found that household car ownership increased employment probabilities of (low-skilled) youth (Painter et al, 2007), in particular when they had access to multiple household cars Perle, 1999, Perle et al, 2002). Similar associations have been found for the Czech Republic (Marada and Květoň, 2016) and among aborigines in rural Taiwan (Lin et al, 2014).…”
Section: Studies Using Individual or Household Car Ownership Measuressupporting
confidence: 83%
“…Three studies further found that household car ownership increased employment probabilities of (low-skilled) youth (Painter et al, 2007), in particular when they had access to multiple household cars Perle, 1999, Perle et al, 2002). Similar associations have been found for the Czech Republic (Marada and Květoň, 2016) and among aborigines in rural Taiwan (Lin et al, 2014).…”
Section: Studies Using Individual or Household Car Ownership Measuressupporting
confidence: 83%
“…The exponential function in this form assigns a weight of three quarters at a time distance of 9.3 minutes and a weight of one-tenth (10%) at a distance of 74.7 minutes. These values can be considered as corresponding to reality (Marada et al 2016). As this model case only deals with rail accessibility and train passengers are generally less sensitive to commuting time than car passengers, the halftime was rounded to 30 minutes for the regional model.…”
Section: Calculation Of Potential Accessibilitymentioning
confidence: 99%
“…On the other hand, compared to American urban environment, most European metropolitan areas have been focusing on developing public transport systems as part of their long-term poli-cies (for more differences, see Pickup and Giuliano, 2005). Many post-communist countries were still witnessing rather generous subsidies for their public transport systems in the beginning of the 1990s, but in recent years their modal-split structure increasingly resembles that reported in Western Europe (e.g., Pucher and Buehler, 2005;Taczanowski, 2015;Król and Taczanowski, 2016;Marada and Květoň, 2016). Thus, the growing dominance of individual transport has led to greater expansion of the motorway network in Central European post-communist societies, including Slovakia with its capital city of Bratislava.…”
Section: Spatial Mismatch Between Places Of Residence and Work And Imentioning
confidence: 99%